Laparoscopic versus Open Appendectomy: A Prospective Comparative Study and 4-Year Experience in a Tertiary Care Hospital - Shaikh, Aftab H.; Tandur, Amarjeet E.; Sholapur, Sachin; Vangal, Gajanan; Bhandarwar, Ajay H.; Ghosh, Ahana; Rathod, Abhishek (The Surgery Journal, 2022)
Background The aim of this study was to validate the pros of laparoscopic appendectomy (LA) over open appendectomy (OA) and to compare various primary outcome measures in the management of acute and recurrent appendicitis.Study Design Prospective comparative study.Place and Duration Between June 2015 and October 2019 in JJ Hospital, Mumbai.Materials and Methods Total of 60 patients with acute and recurrent appendicitis were included in the study. Thirty patients underwent OA and 30 underwent LA. Both groups were comparable clinicopathologically and demographically. Various intraoperative and postoperative parameters were compared. Continuous variables were expressed as mean ± standard deviation and categorical variables were expressed as percentages. Mann–Whitney U test was used to compare continuous variables and chi-squared test was used to compare categorical variables. p-Value≤0.001 was considered to be statistically significant.Results The median age of patients undergoing OA and LA was 24.9 and 25.2 years (p = 0.221), respectively. Female: male ratio in OA and LA was 1.30 and 1.14, respectively (p = 0.795). Mean operative duration in LA and OA group was 47.17 ± 14.39 minutes and 36.9 ± 12.33 minutes (p = 0.001), respectively. Mean length of postoperative stay in LA and OA group was 3.69 ± 0.71 days and 5.28 ± 0.63 days (p = 0.000), respectively. Median visual analogue scale score in LA and OA group was 3.5 and 5 (p = 0.001), respectively. Mean time to return to normal activity in LA and OA group was 8.13 ± 1.33 days and 10.10 ± 2.20 days (p = 0.000), respectively. About 6.66% patients in LA group and 13.33% in OA group had postoperative wound infection (p = 0.652). Mean scar scale scoring done on 30th postoperative day was 4.23 in LA and 8.23 in OA (p = 0.000).Discussion and Conclusion LA is more promising than OA in the management of acute and recurrent appendicitis. LA offers lesser operative site pain in the postoperative period, shorter postoperative hospital stays, earlier recovery, and return to normal activities and cosmetically better scars on 30th day follow-up. No conversions or significant difference in wound related complications were seen in both groups. Prolonged intraoperative duration was the only drawback of LA.
Keywords: laparoscopic; appendectomy; appendicitis; acute; recurrent